DOP019 Immunomodulators reduce the risk of surgery and hospitalisation in Crohn's disease in a prospective European population-based inception cohort: the Epi-IBD cohort. (16th January 2018) - Burisch, J; Andersen, V; Čuković-Čavka, S; Lakatos, P L; D'Inca, R; Magro, F; Arebi, N; Kievit, L; Kaimakliotis, I; Valpiani, D; Katsanos, K H; Vegh, Z; et al.
Abstract: Background: Immunomodulators have both been shown to improve the disease course in IBD patients: however, the literature remains inconsistent. The aim of the study was to investigate the impact of treatment with immunomodulators and biological therapy on disease course and prognosis of patients diagnosed with Crohn's disease (CD) from diagnosis and during the first 5 years of follow-up. Methods: The Epi-IBD cohort is a prospective population-based cohort of 1289 unselected, uniformly diagnosed patients with IBD diagnosed in 2010 in centres from Western and Eastern European countries. Clinical data were captured prospectively throughout the follow-up period. Associations between primary endpoints (surgery and hospitalisation) and covariates were analysed by stepwise Cox regression analysis using the proportional hazards assumption. The use of immunomodulators and biologics were included as time-dependent variables with an initial lag time of 3 months and 2 months, respectively. Results: A total of 488 (38%) patients were diagnosed with CD and included in the study. Patient characteristics are shown in Table 1. Prevalence of treatments on any given day during follow-up is shown in Figure 1. In total, 107 CD patients (22%) had a resection, while 176 (36%) patients were hospitalised because of CD. Treatment with immunomodulators was associated with a reduced risk of surgery (HR: 0.4 CI95% 0.2–0.6) as well as needing hospitalisation (HR: 0.3 CI95% 0.2–0.5) (Figure 2), while biological therapy was not (HR: 0.8 (0.4–1.3) and HR: 0.7 (0.5–1.2)). Other factors included in the regression analusis are shown in Table 2. Conclusions: In this European population-based inception cohort of unselected CD patients, half of the patients were treated with immunomodulators and a fifth of them with biological therapy on any given day during follow-up treatment. Immunomodulators reduced the risk of surgery and hospitalisation, while biological therapy did not.